Learning from agri-environment schemes in Australia. Investing in biodiversity and other ecosystem services on farms - Ansell, Dean; Gibson, Fiona; Salt, David (ANU Press, 2016)
Learning from agri-environment schemes in Australia is a book about the birds and the beef - more specifically it is about the billions of dollars that governments pay farmers around the world each year to protect and restore biodiversity. After more than two decades of these schemes in Australia, what have we learnt? Are we getting the most out of these investments, and how should we do things differently in the future? Involving contributions from ecologists, economists, social scientists, restoration practitioners and policymakers, this book provides short, engaging chapters that cover a wide spectrum of environmental, agricultural and social issues involved in agri-environment schemes.